Hybrid Resilience: The Transformation of Indonesian Islamic Education in Response to Digital Polarization and Global Challenges - St Robiatul Adawiyah; Tri Wahyudi Ramdhan; Yuldashev Azim Abdurakhmonovich (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2026)
In the midst of the escalation of ideological polarization and social segregation due to digital disruption, Islamic educational institutions in Indonesia face a double demand: maintaining religious orthodoxy while responding to the challenges of society 5.0. This research aims to map the transformation of the Islamic education curriculum and pedagogy, moving from the teaching of passive tolerance to the formation of active social resilience. Using the Systematic Literature Review (SLR) approach based on the PRISMA 2020 protocol, this study analyzed 48 selected empirical articles (2015–2025) focusing on the dynamics of Islamic education in post-conflict and multicultural areas. The findings show the emergence of the "Hybrid Resilience" paradigm, in which Islamic Boarding Schools and Madrasas integrate three strategic elements: (1) moderate theology (Wasathiyah), (2) revitalization of social capital based on local wisdom (such as Sintuwu Maroso and Menyama Braya), and (3) the adoption of global values (Sustainable Development Goals/SDGs). This integration creates an inclusive "third space" to reduce radicalism. However, its effectiveness is still hampered by the digital literacy gap among educators. Islamic education is no longer just a moral fortress, but has evolved into an instrument of adaptive social cohesion. Research recommends the need for a "digital peace pedagogy" to reinforce counter-narratives in virtual spaces